Research on “theory of force-center” based on failure characteristics of different roadway sections and its application - Su Hengyu; Luo Chang; Jia Yichao (Scientific Reports)
Abstract In high-stress deep mines prone to rock bursts, the significant deformation of roadway surrounding rock remains a critical scientific issue that urgently requires resolution. In this study, through theoretical analysis and numerical simulations, the failure mechanisms of different roadway sections are investigated, and the “force-center theory” is proposed. This hypothesis is validated by industrial experiments, yielding several key findings: (1) For any cross-sectional shape of the roadway, a unique peripheral circle will be formed, and the damaged area of the roadway section is mainly oriented towards the center of the peripheral circle. (2) During roadway excavation, the stress at any point on the perimeter can be decomposed into a normal stress directed towards the center and a tangential shear stress along the perimeter. The direction of the normal stress plays a crucial role in roadway failure. (3) The effectiveness of roadway reinforcement support lies in the strategic placement of anchor rods and cables along the direction of “external circular stress”. (4) When the external circular method was applied in the high-stress environment of the third soft coal seam in Zhongheng Coal Mine, remarkable results were achieved. The roof-to-floor convergence decreased by 80.34%, and the daily convergence rate decreased by 83.81% accordingly. Additionally, the side convergence decreased by 59.96%, with a 67.50% reduction in the daily rate. This hypothesis provides precise theoretical underpinnings and practical guidance for addressing crucial issues such as the optimal design of roadway sections, the limitations of bolt support schemes (especially in terms of bolt installation angles), and the strategic layout of reinforcement holes.